Метрологические аспекты зубчатых передач - Матюшенко, Николай Васильевич; Федченко, Анна Валерьевна; Шелихова, Инесса Борисовна (НТУ "ХПИ", 2014)
В статье получено уравнение поверхности зубьев цилиндрических передач Новикова с двумя линиями зацепления с циклоидальной продольной формой, нарезанных резцовой головкой. Форма зуба является огибающей однопараметрического семейства мгновенных положений исходного контура инструмента. Построен алгоритм вычисления толщины зуба.

The use of gears with arched teeth belonging to the teeth with a curved longitudinal profile for external engagement instead of helical gears is an effective way to increase the load-bearing capacity, durability and noise reduction when using gears. This article gives an account of a comprehensive analysis and features of the influence of the longitudinal tooth shape on the geometric characteristics. The paper obtained the equation of the teeth of cylindrical gears with two lines Novikov gearing (DLA) with longitudinal cycloidal form, chopped the cutting head. Tooth shape is the envelope of one-parameter family of the instantaneous position of the initial contour of the tool. Constructed an algorithm for calculating the thickness of the tooth.
Metrological aspects gear
Keywords: цилиндрическая передача; передача Новикова; две линии зацепления; толщина зуба; spur gear; gear Novikova; tooth thickness